Cryptocurrency, Mining, and Trading Activities Among Bauchi Muslim Women - Ibrahim, Rahina Musa; Muhammad, Akilu Aliyu (IDRIS Darulfunun Institute, 2026)
This study explores the growing phenomena of cryptocurrency participation among Muslim women in Bauchi, Nigeria, including mining, trading, and related financial activities, and looks at how it affects their financial situation. Digital currencies are revolutionizing financial inclusion on a global scale by giving excluded groups access to alternative investment and income-generating alternatives. However, there is still little research on the use of cryptocurrencies in low-income environments, particularly among culturally restricted populations. This study uses a mixed-methods approach that includes surveys, focus groups, and in-depth interviews with 300 Muslim women involved in e-currency ecosystems. It draws on adaptive diffusion theory and socio-economic inclusion frameworks. The results show that trading cryptocurrencies, especially peer-to-peer (P2P) exchanges, has helped users diversify their sources of income, improve their financial independence, and lessen the effects of inflation and currency devaluation. Despite being limited by capital and energy expenses, mining operations have also given some participants access to specialized revenue sources. The study also highlights important mediators of economic impact, such as financial literacy, access to digital infrastructure, social network support, Islamic ethical considerations around risk and riba, and digital literacy. Concerns regarding market volatility, unclear regulations, and inadequate institutional protections endure despite favorable economic consequences. In addition to providing policy suggestions for inclusive financial literacy programs, community-based regulatory guidelines, and gender-responsive digital economy strategies, the research advances our understanding of the adoption of digital finance in culturally particular contexts.